Cadherin switching in oral squamous cell carcinoma: A clinicopathological study - Ahmed Noaman Ali; Shoukria Mohammed Ghoneim; Esam Rashwan Ahmed; Lubna Omar El-Farouk Abdel Salam; Sanaa Mahmoud Anis Saleh (Elsevier, 2023)
Background and aim: Oral squamous cell carcinoma (OSCC) is one of the most common malignancies worldwide as it represents the sixth most common cancer. Numerous molecular mechanisms have been explained to regulate OSCC progression, including epithelial-mesenchymal transition (EMT). Cadherin switching is the pivotal process that controls EMT in which E-cadherin reduces while N-cadherin elevates. This work aimed to clarify the role of cadherin switching in OSCC. Material and methods: Thirty paraffin-embedded tissue blocks of OSCC including six cases with lymph node metastasis were subjected to immunohistochemical staining using antibodies against E&N-cadherins. Cell cultures were performed using OSCC cell lines (SCC-15/SCC-25) from the human tongue. F-12K medium (Kaighn's Modification of Ham's F12 Medium) was added as EMT inducing media. E&N-cadherin mRNA gene expression levels were detected by real time-polymerase chain reaction (RT-PCR). Results: Cadherin switching through N-cadherin elevation and E-cadherin reduction was evaluated at the histopathologic level in primary and metastatic OSCC as well as at the genetic level within OSCC cell culture. Cadherin switching showed a significant correlation between E&N-cadherins at different histopathological grades of OSCC and in metastatic OSCC. Moreover, the level of mRNA gene expression of E&N-cadherins in human 15 SCC and 25 SCC cell lines with EMT-inducing media exhibited a significant correlation. Conclusions: Cadherin switching is a crucial event in the EMT process. It may be used as a significant tool in the study of OSCC progression. Cadherin switching plays a significant role in the invasion and metastasis of OSCC.